The development of Project-Based Learning Model of the English ability of International Business Administration students at Darussalam Polytechnic Palembang - ariya agustin (Relawan Jurnal Indonesia, 2022)
The purpose of this research is to develop and implement learning models in order to be useful in the learning process. It can make students more active in learning because of the variation in teaching. Development research is used in this research that aims to produce the development of a “Project Based-Learning Model” plus DVD to improve the Students' English Ability in International business administration student of Darussalam Polytechnic. The model of development is adopted by Borg and Gall Model starting from collecting information, development of an initial product, 1st expert validation, 1st product revision, 2nd expert validation, 2nd product revision, tryout, and final product. The Experts’ English Material validation concludes that formulation of learning objective, content, material selection for development of “Project Based- Learning Model” have got a category of Excellent. The validation of the Expert of Media concludes that the final product of DVD has been appropriated with the aspects of learning media that are feasible to be applied.